Patterns of drug treatment in patients with osteoarthritis and chronic low back pain in Japan: a retrospective database study - Akazawa M; Mimura W; Togo K; Ebata N; Harada N; Murano H; Abraham L; Fujii K (Journal of Pain Research, 2019)
Manabu Akazawa,1 Wataru Mimura,1 Kanae Togo,2 Nozomi Ebata,3 Noriko Harada,4 Haruka Murano,5 Lucy Abraham,6 Koichi Fujii31Public Health and Epidemiology, Meiji Pharmaceutical University, Tokyo, Japan; 2Corporate Affairs, Health & Value, Pfizer Japan Inc., Tokyo, Japan; 3Medical Affairs, Pfizer Japan Inc., Tokyo, Japan; 4Clinical Research, Pfizer R&D Japan G.K., Tokyo, Japan; 5Clinical Research Professionals, Clinical Study Support Inc., Nagoya, Japan; 6Patient & Health Impact, Pfizer Ltd., Surrey, UKPurpose: Musculoskeletal diseases, including osteoarthritis (OA) and low back pain (LBP), are the leading causes of years lived with disability, and are associated with lowered quality-of-life, lost productivity, and increased healthcare costs. However, information publicly available regarding the Japanese real-world usage of prescription medications is limited. This study aimed to describe the clinical characteristics of patients with OA and chronic LBP (CLBP), and to investigate the patterns of medications and opioid use in Japanese real-world settings.Materials and methods: A retrospective study was conducted using a Japanese administrative claims database between 2013 and 2017. The outcomes were patient characteristics and prescription medications, and they were evaluated separately for OA and CLBP.Results: The mean age of 118,996 patients with OA and 256,402 patients with CLBP was 68.8±13.1 years and 64.8±16.4 years, respectively. Approximately 90% of patients with OA and CLBP were prescribed non-steroidal anti-inflammatory drugs (NSAIDs). Other prescriptions included hyaluronate injection (35.6%), acetaminophen (21.4%), and steroid injection (20.0%) in patients with OA, and pregabalin (39.0%) and acetaminophen (22.4%) in patients with CLBP. Weak opioids were prescribed to 10.7% and 20.6% of patients with OA and CLBP, respectively. The prescription of COX-2 inhibitors (OA: +6.5%; CLBP: +6.7%) and acetaminophen (OA: +16.4%; CLBP: +14.4%) increased between 2013 and 2017. The first commonly prescribed medication among patients with OA and CLBP were NSAIDs; hyaluronate injection (patients with OA) and pregabalin (patients with CLBP) were also common first-line medications. Acetaminophen, steroid injection (patients with OA), and weak opioids were prescribed more in the later phases of treatment.Conclusion: Most patients were prescribed limited classes of pain drugs, with NSAIDs being the most common pain medication in Japan for patients with OA and CLBP. Opioid prescription was uncommon, and were weak opioids when prescribed.Keywords: osteoarthritis, chronic low back pain, non-steroidal anti-inflammatory drugs, opioid, pain